(3GbJUGOjGJ Gdfbd GdHMQjs - (3CMeO YHO GdefUa(B, (3eMehOs ((3GdGScfOQjI(B:s (3ecJHI heWHYI GdGTYGY GdafjI(B,s, 2001)
(3GbJUGOjGJ Gdfbd(B-(3GdJcGdja(B-(3GdShb GdedGMj(B-(3YbO GdGYGQI chSjdI dJehjd MjGRI GdSaf(B-(3GdSjGSGJ GdHMQjI(B-(3LgGR GdeThQIs
(3edGMb (B233(3U(B.s
Keywords: (3GdGbJUGOs; (3GdHhGNQs; (3Gdfbds